THE RISK FACTORS FOR INITIAL REPRODUCTIVE LOSS - Лебедева, Екатерина Игоревна; Бельницкая, Ольга Александровна; Кравцова, Елена Станиславовна; Мегрелидзе, Елена Викторовна; Горбачева, Татьяна Ивановна (Mother and Baby in Kuzbass, 2017)
Objective. 196 patients with initial reproductive loss and 123 patients with favorable outcomes of their pregnancy as a control group. The purpose of our research – to detect genetic, clinical and paraclinical risk factors for initial reproductive loss. Methods. Analysis of anamnestic data, clinical and standard lab tests results was made, in addition we evaluated hemostasiogram indices, homocysteine level, molecular genetic analysis for 4 genes coded components of hemostasis and folate cycle. Statistically significance is attained when a p-value less then 0,05. Results. The risk factors for initial pregnancy loss was determined as somatic and gynecological burden, inherited thrombogenic risk factors such as burdened familial history in thrombophilia and arterial hypertensia, existence of arterial hypertensia, hypercoagulation syndrome, deaggregating thrombocytopathy, hyperhomocysteinemia and homozygous care of genes responsible for fibrinolysis and folate exchange, and acquired thrombogenic risk factors such as nicotine dependence and hormonal contraception. Conclusion. Mixed somatic and gynecological pathology, abnormalities in hemostasis, combination of inherited and acquired thrombogenic risk factors dominates in women with initial reproductive loss, though only 37,3 % such pregnancies have favorable outcome.